2016
DOI: 10.1371/journal.pone.0146620
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of a New Rapid PCR Assay for Detecting Influenza Virus in an Emergency Department and Hospitalized Patients

Abstract: Seasonal influenza causes significant morbidity and mortality and has a substantial economic impact on the healthcare system. The main objective of this study was to compare the cost per patient for a rapid commercial PCR assay (Xpert® Flu) with an in-house real-time PCR test for detecting influenza virus. Community patients with influenza like-illness attending the Emergency Department (ED) as well as hospitalized patients in the Hospital Clínic of Barcelona were included. Costs were evaluated from the perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 16 publications
2
24
0
1
Order By: Relevance
“…Trabattoni et al (4.2 vs 6.1 hours, P = 0.03) and Abanses et al (2.6 vs 3.3 hours, 95% CI, 0.32‐1.00) demonstrated decreased mean ED LOS in prospective studies comparing POCT vs standard testing over a single influenza season. Similarly, in two retrospective studies comparing post‐ and pre‐POCT implementation, Soto et al reported a reduced mean ED LOS (20.7 vs 28.1 hours, P = 0.003) as did Rogers et al (4.3 vs 4.7 hours, P < 0.002). Fernandez et al also demonstrated a significant decrease in ED LOS, in this case between POCT(+) and POCT(−) patients (3.6 vs 7.84 hours, P < 0.01).…”
Section: Resultsmentioning
confidence: 73%
“…Trabattoni et al (4.2 vs 6.1 hours, P = 0.03) and Abanses et al (2.6 vs 3.3 hours, 95% CI, 0.32‐1.00) demonstrated decreased mean ED LOS in prospective studies comparing POCT vs standard testing over a single influenza season. Similarly, in two retrospective studies comparing post‐ and pre‐POCT implementation, Soto et al reported a reduced mean ED LOS (20.7 vs 28.1 hours, P = 0.003) as did Rogers et al (4.3 vs 4.7 hours, P < 0.002). Fernandez et al also demonstrated a significant decrease in ED LOS, in this case between POCT(+) and POCT(−) patients (3.6 vs 7.84 hours, P < 0.01).…”
Section: Resultsmentioning
confidence: 73%
“…Although our current study was not designed to evaluate rapid POC-PCR impact on ED LOS, our prior study suggests ED LOS reduction by 33 min if POC-PCR is performed during post-rooming ED evaluation, with potential for further reduction if POC-PCR is performed at triage [34]. Additional clinical impact includes reduced ancillary diagnostic testing and costs [30,[27][28][29]. Future studies are needed to ascertain if decreasing ED LOS may reduce disease transmission by limiting contact time and to assess POC-PCR cost-effectiveness at triage during both peak and non-peak ARI season.…”
Section: Discussionmentioning
confidence: 97%
“…Rapid POC-PCR also reduces hospital admissions and improves the appropriate use of antimicrobials in clinic and hospitalized patients [26]. In pediatric settings, POC-PCR decreases ancillary testing such as chest X-rays and urine analyses [27,28] and saves costs, especially when multiple viruses are tested simultaneously [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…When standard PCR was used, in contrast, our findings suggest that these decisions were made before the test results were available. The possible benefits of not admitting patients to hospital, beyond those for individual patient management, include better infection control and outbreak prevention, as well as reduced demands on hospital resources . The impact of rapid PCR testing on outbreak prevention and infection control measures should be evaluated.…”
Section: Discussionmentioning
confidence: 99%